Utilizing Communicative Language Games to Improve Students’ Speaking Ability - Siti Maryam (Journal of Languages and Language Teaching, 2020)
This study is aimed at finding the utilizing of communicative language games in improving students' speaking ability at second grade students of SMPN 4 Praya Barat Daya. This study was an action research which comprised two cycles. It involved an English teacher and 24 students of second grade at SMPN 4 Praya Barat Daya. The steps of this study were reconnaissance, planning the actions, implementing and observing the actions, and reflecting the actions done. The data of this study were qualitative and quantitative. The qualitative data were obtained by observing the teaching and learning process during the implementation of the actions and interviewing the students and the English teacher. The data were collected using field notes and interview transcription. The quantitative data were taken by assessing the students speaking ability using pre-test and post-test in the form of students' scores. The research finding shows that the use of the communicative language games is effective to improve students' speaking ability. The games are accompanied with other actions such as using classroom English, applying varied themes, using adequate media, doing language form activities, giving feedback, giving rewards, doing group works and rearranging the students seating arrangement. Therefore, it can be concluded that the use of communicative language games is able to improve students' speaking skills at second grade students of SMPN 4 Praya Barat Daya.